Superunitary operator and BRST transformations of a non-Abelian two-form. (26th February 2018) - Shukla, Dheeraj; Kumar, Kuldeep
Abstract: Using the superunitary operator approach, we derive (anti-)BRST symmetry transformations for the non-Abelian 2-form gauge theories by studying the gauge symmetries of a new Lagrangian which involves coupling of matter fields not only to 1-form field but also to a 2-form field.